The role of high-tech certification in enterprise green innovation: from the perspectives of substantive innovation and strategic innovation - Liang, Zhiqiang; Shen, Yao; Yang, Kunyu; Kuang, Jinsong (Frontiers in Environmental Science, 2025)
Sustainable development comes from a balance between economic growth and environmental protection, with due consideration of long-term impacts on environment. Leveraging policy tools to promote green innovation is a critical strategy for achieving this objective. This paper examines the impact of high-tech certification on corporate green innovation, distinguishing between substantive and strategic green innovation. It develops a theoretical framework to analyze how high-tech certification influences enterprise green innovation through mechanisms such as tax preferences, government subsidies, financing constraints, and leveraging capital market attention. The study employs a zero-inflated negative binomial regression model and utilizes data of A-share listed companies from 2006 to 2023 to systematically assess the impact of high-tech certification on enterprise green innovation strategies, underlying mechanisms, and their heterogeneity. The research discovers that in general, high-tech certification significantly promotes enterprise green innovation, having a more prominent facilitating effect on strategic green innovation, resulting in a certain degree of green patent false prosperity. From the perspective of underlying mechanisms, high-tech certification increases the resources actually obtained by enterprises through tax preferences and government subsidies and alleviates financing constraints, thereby guiding enterprises to undertake more substantive green innovation; while enhancing capital market attention increases the expected resources obtained by enterprises, prompting enterprises to be more inclined towards strategic green innovation. Further analysis reveals that the impact of high-tech certification on corporate green innovation varies significantly across different ownership structures, industries, and regions. Specifically, in state-owned enterprises, technology-intensive sectors, and enterprises located in the central regions, the positive effect on substantive green innovation is particularly pronounced. This study contributes to the literature on policy tools and corporate green innovation strategies by offering robust empirical evidence to optimizing policy design, mitigating policy arbitrage, and preventing patent bubbles.